New flare minimization strategies with consideration of multi-plant material exchange. (1st February 2021) - Xu, Yiling; Yu, Li; Wang, Sujing; Xu, Qiang; Ho, Thomas C.
Abstract: Flare emissions during chemical plant turnaround operations, such as start-up and shutdown, will waste tremendous material and energy while emit huge amounts of carbon dioxide, volatile organic compounds, oxides of nitrogen, and carbon monoxide. Thus, flare minimization is a triple-win thrust toward simultaneous industrial, environmental, and societal sustainability. Available flare minimization studies are exclusively focused on single process facility plant or single plant, which have substantially restricted flare minimization capabilities of many chemical plants. In this paper, new turnaround flare minimization strategies with considerations of multi-plant material exchanges have been developed. The novelty of the study is that flaring sources of one plant, which might be very difficult or expensive for recovery by the plant itself, could be effectively and efficiently utilized by another adjacent plant who is under its normal production, so that flare emissions can be significantly reduced than ever before. Two case studies have been provided: one is flare minimization during an olefin plant start-up supported by a normal operating plant; the other is flare minimization during an olefin plant shutdown supported by a normal operating plant. Through virtual demonstration via plant-wide dynamic modeling and simulations, the new start-up and shutdown flare minimization strategies could save 83.64% and 90.23% of original flaring sources, respectively. This study has laid out a new foundation for future flare minimization studies with consideration of multi-plant material exchanges. It could provide an augmented degree of opportunities for cost-effective industrial emission reductions and controls.